Assessment of natural variation in the first pore domain of the tomato HKT1;2 transporter and characterization of mutated versions of SlHKT1;2 expressed in Xenopus laevis oocytes and via complementation of the salt sensitive athkt1;1 mutant - Almeida, Pedro M. F.; de Boer, Gert-Jan; de Boer, Albertus H. (Frontiers in Plant Science, 2014)
Single Nucleotide Polymorphisms (SNPs) within the coding sequence of HKT transporters are important for the functioning of these transporters in several plant species. To unravel the functioning of HKT transporters analysis of natural variation and multiple site-directed mutations studies are crucial. Also the in vivo functioning of HKT proteins, via complementation studies performed with athkt1;1 plants, could provide essential information about these transporters. In this work, we analysed the natural variation present in the first pore domain of the HKT1;2 coding sequence of 93 different tomato accessions, which revealed that this region was conserved among all accessions analysed. Analysis of mutations introduced in the first pore domain of the SlHKT1;2 gene showed, when heterologous expressed in Xenopus laevis oocytes, that the replacement of S70 by a G allowed SlHKT2;1 to transport K+, but also caused a large reduction in both Na+ and K+ mediated currents. The study of the transport characteristics of SlHKT1;2 revealed that Na+-transport by the tomato SlHKT1;2 protein was inhibited by the presence of K+ at the outside of the membrane. GUS expression under the AtHKT1;1 promoter gave blue staining in the vascular system of transgenic Arabidopsis. athkt1;1 mutant plants transformed with AtHKT1;1, SlHKT1;2, AtHKT1;1S68G and SlHKT1;2S70G indicated that both AtHKT1;1 and SlHKT1;2 were able to restore the accumulation of K+ in the shoot, although the low accumulation of Na+ as shown by WT plants was only partially restored. The inhibition of Na+ transport by K+, shown by the SlHKT1;2 transporter in oocytes (and not by AtHKT1;1), was not reflected in Na+ accumulation in the plants transformed with SlHKT1;2. Both AtHKT1;1-S68G and SlHKT1;2-S70G were not able to restore the phenotype of athkt1;1 mutant plants.